Levelling the Field : Improving Opportunities for Women Farmers in Africa - World Bank; ONE Campaign (World Bank, Washington, DC, 2014)
There is a growing recognition of agriculture's potential to spur growth and reduce poverty in Africa. Agriculture accounts for one-third of the continent's gross domestic product (GDP), and two-thirds of its citizens rely on the sector for their incomes. Investments in agriculture will hence not only improve productivity and the continent's ability to feed a growing population, but will also lift families out of poverty. Over 90 percent of sub-Saharan Africa's extreme poor are engaged in agriculture, and growth originating in the sector is 2-4 times more effective at directly reducing poverty than growth originating in other sectors. Yet agriculture in Africa has not fulfilled its potential, suffering from a lack of investment and insufficient attention from policy-makers. A key hindrance to agricultural development and broader growth is a wide and pervasive gender gap in agricultural productivity. Women comprise nearly half of the labor force in Africa's agriculture sector, and more than half in several countries, but on the whole they produce less per hectare than men. Existing evidence from small-scale studies across the continent documents the numerous disadvantages that women face in accessing the same resources, training, markets and opportunities as men. They also face ingrained norms and institutional barriers that further widen the gap. Tackling the barriers that hold back the productivity of female farmers could both enhance gender equality and usher in broader economic growth. The African Union has declared 2014 to be the 'year of agriculture and food security', bringing much needed attention to the sector's potential to transform the continent. This is an opportunity not only to revitalize the agriculture sector, but to rally African governments and development organizations to commit to concrete policy action to redress the inequalities within the sector, and in so doing to reap greater rewards from future investments.